Stereotactic body radiotherapy (SBRT) for multiple pulmonary oligometastases: Analysis of number and timing of repeat SBRT as impact factors on treatment safety and efficacy. Issue 2 (May 2018) - Klement, R.J.; Hoerner-Rieber, J.; Adebahr, S.; Andratschke, N.; Blanck, O.; Boda-Heggemann, J.; Duma, M.; Eble, M.J.; Eich, H.C.; Flentje, M.; Gerum, S.; Hass, P.; et al.
Abstract: Background: Stereotactic body radiotherapy (SBRT) for oligometastatic disease is characterized by an excellent safety profile; however, experiences are mostly based on treatment of one single metastasis. It was the aim of this study to evaluate safety and efficacy of SBRT for multiple pulmonary metastases. Patients and methods: This study is based on a retrospective database of the DEGRO stereotactic working group, consisting of 637 patients with 858 treatments. Cox regression and logistic regression were used to analyze the association between the number of SBRT treatments or the number and the timing of repeat SBRT courses with overall survival (OS) and the risk of early death. Results: Out of 637 patients, 145 patients were treated for multiple pulmonary metastases; 88 patients received all SBRT treatments within one month whereas 57 patients were treated with repeat SBRT separated by at least one month. Median OS for the total patient population was 23.5 months and OS was not significantly influenced by the overall number of SBRT treatments or the number and timing of repeat SBRT courses. The risk of early death within 3 and 6 months was not increased in patients treated with multiple SBRT treatments, and no grade 4 or grade 5 toxicity was observed in these patients. Conclusions: In appropriately selected patients, synchronous SBRT for multiple pulmonary oligometastases and repeat SBRT may have a comparable safety and efficacy profile compared to SBRT for one single oligometastasis.